Between good and ghetto: African American girls and inner-city violence - Jones, Nikki (The Rutgers series in childhood studies, 2010)
The social world of inner city girls -- "It's not where you live, it's how you live" : when good girls fight -- "Ain't I a violent person?" : understanding girl fighters -- "Love make you fight crazy" : dating violence and inner city girls